CHINESE AND PHILANTHROPY: THE ROLE OF THE CHINESE COMMUNITY IN HUMANITARIAN CHARITABLE INSTITUTIONS IN SEMARANG 1920-1950: Tionghoa dan Filantropi: Peran Komunitas Tionghoa Dalam Lembaga Amal Kemanusiaan di Semarang 1920-1950 - Muhammad Yanuar Rizki; Mukhamad Shokheh (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to explain the role of the Chinese community in humanitarian charities in Semarang from the 1920s to the 1950s in the context of colonial segregation, war, and early Indonesian independence. Using historical research methods including heuristics, source criticism, interpretation, and historiography, the research analyzes archival documents, newspapers, and secondary literature to understand the evolution of humanitarian organizations founded by Chinese. Drawing on philanthropy theory and social capital theory, the study highlights how institutions such as Boen Hian Tong, Tiong Hoa Hwee Koan (THHK), Polikliniek Tionghoa, and St. Mary's Hall adapted and transformed through three major regimes: Dutch colonial rule, Japanese occupation, and the early Republic. These organizations not only served immediate communal needs but also laid the foundation for inclusive social welfare through education, health care, and mutual aid. A key finding is the strategic shift from ethnically exclusive charities to more open and cooperative institutions that were able to respond to changing socio-political pressures. The novelty of this research lies in its exclusive focus on the philanthropic ecosystem of the Chinese community in Semarang, its integrated analysis of cross-sectoral institutions, and the application of a dual theoretical framework to uncover community resilience and agency.